Characterisation of polyhydroxyalkanoate production by mutant Azotobacter vinelandii - Mok, Pei Shze; Sudesh Kumar,; Liew, Pauline Woan Ying; Jong, Bor Chyan; Najimudin Nazalan, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The production of PHA by Azotobacter vinelandii was characterised in different types of mineral medium including DSMZAzotobacter medium, Ashby’s medium, Burk’s medium and Minimal Medium PHA (MMPHA). A deletion mutant of Azotobacter vinelandii, designated as ΔAvin_16040 was able to accumulate 3-folds higher PHA which was 0.48 ± 0.02 g/L compared to the wild type strain which was 0.11 ± 0.03 g/L in a modified DSMZ-Azotobacter medium. Although this bacterial strain is able to fix nitrogen, addition of urea as external nitrogen source into the medium had increased both its biomass and PHA production. Among the various medium types, MMPHA showed the highest biomass and PHA yields of 3.5 ± 0.1 g/L and 1.50 ± 0.03 g/L, respectively. Higher PHA concentration of 1.74 ± 0.05 g/L was obtained in this medium by increasing the sucrose concentration from 20 g/L to 25 g/L.